Distribution pattern and biochemical variability of Irish invasive seaweed across a spatial gradient. - Zanolla-Balbuena, Maríanela Fernanda; Cara-Ortega, Claudia; Sanz-Fernández, Víctor; Stengel, Dagmar B. (Elsevier, 2025)
This study updates the distribution of seaweed invasive alien species (IAS) in Ireland and demonstrates the natural spatial variation of their phenolic compounds and fatty acid profiles, coupled with an assessment of biomass availability. We examined the intertidal area of 68 coastal locations and detected the presence of six IAS, but abundant populations (30–50 % cover) were only recorded for Sargassum muticum in some western and southern locations along the Irish coast. However, the fact that so many invasive species were widely distributed represents a dormant threat to Irish coastal ecosystems. Regarding distribution, we detected a spatial expansion of Colpomenia peregrina and Codium fragile, while a contraction was recorded for S. muticum and Asparagopsis armata. Undaria pinnatifida represents a recent introduction, and Gracilaria vermiculophylla is spreading to new locations in the south and west. In general, saturated fatty acid content was high in C. fragile and C. peregrina samples, and higher monounsaturated fatty acid content occurred in the latter. Sargassum muticum and G. vermiculophylla presented more polyunsaturated fatty acids and n-3 fatty acids (together with C. fragile). Statistical analyses showed that, for to S. muticum, higher water temperatures decreased metabolite content in all areas sampled, and higher concentrations of metabolites were generally found in northern populations. However, biomass was not abundant at these sites, which poses challenges facing valorisation of these natural resources. This study provides important baseline information of fatty acid profiles and phenolic content of Irish IAS, an essential preliminary step in industrial sourcing of marine bioactive metabolites.
Keywords: Algas marinas - Distribución geográfica; Productos naturales marinos; Especies exóticas invasoras; Codium; Colpomenia; Gracilaria; Ireland; Natural products; Sargassum; Valorisation